(untitled) (INNOVATIVE ECONOMY, 2025)
Vysotskyi K.R. EUROPEAN INTEGRATION IN THE CONTEXT OF REGIONAL SECURITY CHALLENGES Purpose. The aim of the article is to study the threats and security challenges for the countries of the European Union that have arisen in connection with Russia’s military aggression against Ukraine, and to identify the prospects that European integration opens up for conflict resolution. Methodology of research. General scientific and specific methods of scientific research were used to achieve this set goal, such as problem analysis and synthesis of solutions – to identify individual risks to the EU’s stability and study the measures taken to overcome the dangers; dialectical method of scientific knowledge – to consider the essence of the components of the EU’s economic stability; abstract and logical – to develop measures to ensure Ukraine’s economic stability, taking into account the experience of European countries. The methodological basis of the study is the scientific works of foreign and domestic scientists, legal acts of the EU institutions, statistics and materials of Internet resources on economic resilience, economic resilience, critical infrastructure security, and cybersecurity. Findings The article examines the transformation of approaches to ensuring the security and economic stability of the European Union in the context of full-scale Russian aggression against Ukraine. The historical and modern aspects of European integration as a tool for strengthening regional security are analysed, in particular in the context of the formation of a common EU defence policy. It is established that the European Economic Security Strategy considers a comprehensive approach in the current, geopolitical and technological space, which is constantly changing. This approach includes the identification, assessment and management of risks to the economic security of the EU. The war in Ukraine became a catalyst for the revision of the EU’s security priorities, which led to the adoption of new strategic documents, in particular the “Strategic Compass” and the European Defence Industrial Strategy (EDIS). Considering the prospects for the integration of Ukraine’s economy into the EU and the need to restore the economic complex in wartime, it is advisable to diversify energy sources and supply chains of critical raw materials, and increase energy efficiency. Originality. The scientific novelty of the research results lies in the conceptual substantiation of the role of European integration as a mechanism for resolving security conflicts in the region. The study proves that the EU integration model, in particular the combination of security policy with economic interdependence, is capable of forming a new architecture of peaceful coexistence in the conditions of the modern international system focused on national interests. Practical value. The proposals presented in the paper for strengthening the economic stability of Ukraine, developed on the basis of European experience, can be used in the preparation of legislative and regulatory acts, and included in strategic programs and programs of social and economic development at both the state and regional levels. Key words: European integration, regional security, energy security, cybersecurity, economic security, EU, threats, security policy.